Compétence de la prononciation des voyelles nasales chez les élèves de SMA Negeri 1 Sunggal - Nabilla Ummi Shopia; Andi Wete Polili (Universitas Negeri Semarang, 2026)
This research examines the proficiency of students at SMA Negeri 1 Sunggal in pronouncing French nasal vowels ([ɑ̃], [ɛ̃], [oẽ], [ɔ̃]). The problem identified is the numerous pronunciation errors students make, creating a discrepancy between their speech and French phonetic norms. The methodology adopted is a qualitative descriptive approach, using an oral expression test as a research tool. The study focuses on 66 senior high school students in the 2025/2026 school year. The results reveal that the students’ pronunciation of nasal vowels does not meet French phonetic standards. The articulation produced by the students deviates from standard phonetic expectations. This research highlights the need for an in-depth study of nasal vowels to improve the phonetic skills of high school students, particularly in their production in accordance with French standards. In conclusion, students at SMA Negeri 1 Sunggal have significant difficulty mastering French nasal vowels, requiring targeted educational reinforcement to meet the required phonetic standards.